Implementing Stunting Prevention Through Nutritional Fulfillment of Children and the Role of the Family - Dini Afriani; Azizah Nur Astuti (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Stunting is a disruption in the growth and development of children due to chronic lack of nutrition and recurrent infections, which is characterized by their body length or height being below the exact standards set by the minister who administers government affairs in the health sector. In Sukawening Village, Ganeas District, Sumedang Regency at the beginning of 2023 there were 20 people and at the end of 2023 the stunting rate in Sukawening Village decreased to 16 people. This community service implementation aims to help mothers to increase their knowledge about stunting so that they are able to know about the dangers of stunting and the need for lifestyle changes to prevent stunting. This community service activity was carried out in January 2024. The focus of this community service activity is increasing the knowledge of mothers in Sukawening Village regarding stunting in an effort to prevent stunting behavior that attacks newborn children up to 5 years of age. The counseling was carried out offline, with the delivery of material and also discussions in the form of questions and answers with cadre mothers and mothers of stunted children in Sukawening Village, Ganeas District, Kab. Sumedang. This activity went smoothly and the mothers were very enthusiastic about listening to the counseling process